A Phenomenological Study of Ethnic Entrepreneurship and Business Sustainability among Young MSME Entrepreneurs - Hastin Umi Anisah Hastin; Aufa Habibie; Muhammad Afrimal Firdaus (At-Taradhi Jurnal Studi Ekonomi, 2025)
This study aims to provide a comprehensive understanding of the implementation of ethnic entrepreneurship among young MSME entrepreneurs in Banjarmasin City. Specifically, it seeks to explore the phenomenon of ethnic entrepreneurship and to examine whether its application influences the sustainability of young entrepreneurs’ MSMEs in the city. Data were collected from five key informants selected through a snowball sampling technique. The research employed passive participant observation, semi-structured interviews, and both open- and closed-ended questionnaires as data collection instruments. Emphasizing an emic perspective, the study prioritized the perceptions and experiences of the key informants. A phenomenological analytical approach, as proposed by Miles and Huberman, was utilized to interpret the data. The findings reveal that ethnic entrepreneurship significantly contributes to the sustainability of young entrepreneurs’ MSMEs in Banjarmasin City.